Ionic Modification Turns Commercial Rubber into a Self-Healing Material - Das, Amit; Sallat, Aladdin; Boehme, Frank; Suckow, Marcus; Basu, Debdipta; Wiessner, Sven; Stoeckelhuber, Klaus Werner; Voit, Brigitte; Heinrich, Gert (ACS Applied Materials and Interfaces, 2015)
Invented by Charles Goodyear, chemical cross-linking of rubbers by sulfur vulcanization is the only method by which modern automobile tires are manufactured. The formation of these cross-linked network structures leads to highly elastic properties, which substantially reduces the viscous properties of these materials. Here, we describe a simple approach to converting commercially available and widely used bromobutyl rubber (BIIR) into a highly elastic material with extraordinary self-healing properties without using conventional cross-linking or vulcanising agents. Transformation of the bromine functionalities of BIIR into ionic imidazolium bromide groups results in the formation of reversible ionic associates that exhibit physical cross-linking ability. The reversibility of the ionic association facilitates the healing processes by temperature- or stress-induced rearrangements, thereby enabling a fully cut sample to retain its original properties after application of the self-healing process. Other mechanical properties, such as the elastic modulus, tensile strength, ductility, and hysteresis loss, were found to be superior to those of conventionally sulfur-cured BIIR. This simple and easy approach to preparing a commercial rubber with self-healing properties offers unique development opportunities in the field of highly engineered materials, such as tires, for which safety, performance, and longer fatigue life are crucial factors.
CRIS-Team Scopus Importer:2023-03-20
Keywords: bromobutyl rubbers; elastomers; ionic associations; network structures; self-healing